2014
DOI: 10.1152/ajplung.00180.2014
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette smoke extract affects mitochondrial function in alveolar epithelial cells

Abstract: Ballweg K, Mutze K, Königshoff M, Eickelberg O, Meiners S. Cigarette smoke extract affects mitochondrial function in alveolar epithelial cells. Am J Physiol Lung Cell Mol Physiol 307: L895-L907, 2014. First published October 17, 2014 doi:10.1152/ajplung.00180.2014.-Cigarette smoke is the main risk factor for chronic obstructive pulmonary disease (COPD). Exposure of cells to cigarette smoke induces an initial adaptive cellular stress response involving increased oxidative stress and induction of inflammatory s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
86
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 111 publications
(93 citation statements)
references
References 53 publications
4
86
0
Order By: Relevance
“…While there is no doubt that increased ROS level and disturbed anti-oxidant protection contributes to the onset and progression of COPD [92], the exchange of mitochondrial function beyond its role as ROS generators is not yet solved. Recent data indicate that cigarette smoke alters mitochondrial structure and function but this appears to depend upon cell type and extent of damage [93,94]. A recent study strongly indicates the disposal of smoke-damaged mitochondria via the PINK1/Parkin-mediated autophagy route as PINK1 knock-out mice were protected against mitochondrial dysfunction and smoke-induced emphysema formation [95].…”
Section: Mitochondrial Dysfunctionmentioning
confidence: 99%
“…While there is no doubt that increased ROS level and disturbed anti-oxidant protection contributes to the onset and progression of COPD [92], the exchange of mitochondrial function beyond its role as ROS generators is not yet solved. Recent data indicate that cigarette smoke alters mitochondrial structure and function but this appears to depend upon cell type and extent of damage [93,94]. A recent study strongly indicates the disposal of smoke-damaged mitochondria via the PINK1/Parkin-mediated autophagy route as PINK1 knock-out mice were protected against mitochondrial dysfunction and smoke-induced emphysema formation [95].…”
Section: Mitochondrial Dysfunctionmentioning
confidence: 99%
“…mitochondrial OXPHOS (15,16), whereas treatment with nontoxic doses of CS increases mitochondrial metabolic activity (17,18), inducing a metabolic shift from glucose (glycolysis) to palmitate (β-oxidation) metabolism (18). Loss of acetyl-CoA and the Krebs cycle intermediate succinate is observed in basal cells of smokers (19).…”
Section: Bioenergetics and Nutrient Sensingmentioning
confidence: 99%
“…35 and Figure 2). Hyperfusion has been documented in COPD and in lung cancer (17,18,37,38), whereas loss of fusion, specifically loss of MFN2, has been associated with lung cancer (38) and PH (39). The role of mitochondrial fission and fusion in lung cancer may be microenvironment specific; increased fission may allow cancer cells to proliferate rapidly and invade the surrounding tissue, while increased fusion may allow for cell survival during times of stress or drug toxicity (27).…”
Section: Bioenergetics and Nutrient Sensingmentioning
confidence: 99%
“…However, autophagy is supposedly specific to cell type and, thus, in alveolar macrophages in COPD patients, there appears to be a selective defect in autophagy resulting in impaired clearance of damaged and dysfunctional mitochondria [69]. After treatment with cigarette smoke, recent studies have shown altered mitochondrial structure (elongation) and function in alveolar epithelial cells [70], and in primary bronchial epithelial cells [71]. By contrast, HARA et al [72] demonstrated mitochondrial fragmentation in primary human bronchial epithelial cells upon stimulation with cigarette smoke extract for 48 h. It has been suggested that while mitochondria initially adapt to cigarette smoke and oxidative stress by altering their structure, this may be not beneficial in the long term due to a resultant decrease in mitophagy [70].…”
Section: Autophagy/mitophagymentioning
confidence: 99%
“…After treatment with cigarette smoke, recent studies have shown altered mitochondrial structure (elongation) and function in alveolar epithelial cells [70], and in primary bronchial epithelial cells [71]. By contrast, HARA et al [72] demonstrated mitochondrial fragmentation in primary human bronchial epithelial cells upon stimulation with cigarette smoke extract for 48 h. It has been suggested that while mitochondria initially adapt to cigarette smoke and oxidative stress by altering their structure, this may be not beneficial in the long term due to a resultant decrease in mitophagy [70]. Recently, AHMAD et al [73] proposed a pathway of smoke-induced cellular senescence due to impaired mitophagy.…”
Section: Autophagy/mitophagymentioning
confidence: 99%